Effective Transmission Modulation at Telecommunication Wavelengths through Continuous Metal Films Using Coupling between Borophene Plasmons and Magnetic Polaritons. Issue 7 (25th January 2021) - Nong, Jinpeng; Feng, Fu; Min, Changjun; Yuan, Xiaocong; Somekh, Michael
Abstract: Optical modulation has been recognized as one of the most important operations in photonics. The use of 2D materials that support highly confined plasmonic modes allows one to manipulate light at the extreme subwavelength scale, thus significantly shrinking the size of the modulator, with potential for major advances in the state of art of existing devices. Here, a prototype plasmonic modulator is theoretically presented for the effective transmission modulation through a continuous metal film enabled by the strong coupling between anisotropic borophene surface plasmonic (BSP) modes and magnetic polaritons (MP) modes. Simulations reveal that plasmonic absorption in borophene within the grating slits can efficiently suppress the extraordinary optical transmission induced by the MP mode, resulting in the effective transmission modulation. By dynamically tuning the borophene electron density to decouple or couple BSP mode with MP mode, high modulation efficiency of 98.6% at 1550 nm can be achieved for borophene along both crystal axes, indicating excellent performance of the designed modulator via such mechanism. These results illustrate the potential of strong BSP–MP coupling as a promising strategy to realize the transmission modulation for optoelectronic applications. Abstract : A plasmonic modulator is theoretically presented for the transmission modulation through a continuous metal film. Extraordinary optical transmission through the metal film can be achieved, which is then suppressed by exciting borophene plasmons. High modulation efficiency of 98.6% at 1550 nm can be achieved by dynamically tuning the borophene electron density to decouple or couple borophene plasmonic mode with magnetic polaritons mode.